Electrode layer
Patent Information
- Application Number
- JP2022000470
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-01-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-01-05
AI Technical Summary
【0017】 本開示においては、容量維持率が良好な電極層を提供できるという効果を奏する。
Smart Images

Figure 0007644034000005 
Figure 0007644034000001 
Figure 0007644034000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode layer. [Background technology]
[0002] An all-solid-state battery is a battery having a solid electrolyte layer between a positive electrode layer and a negative electrode layer, and has the advantage that it is easier to simplify safety devices compared to liquid batteries having an electrolyte solution containing a flammable organic solvent. For example, Patent Document 1 discloses a solid electrolyte composition containing an inorganic solid electrolyte, a binder, and a dispersion medium. Patent Document 1 further discloses a solid electrolyte composition containing an inorganic solid electrolyte, a binder, and a dispersion medium, the solubility parameter of which is 21 MPa. 1 / 2 The following is disclosed. Patent Document 2 also discloses that butyl butyrate is used as a dispersion medium when the positive electrode layer and the negative electrode layer are produced. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 203334 [Patent Document 2] JP 2021-132010 A Summary of the Invention [Problem to be solved by the invention]
[0004] In order to improve the performance of all-solid-state batteries, an electrode layer having a good capacity retention rate is required. The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide an electrode layer having a good capacity retention rate. [Means for solving the problem]
[0005] In the present disclosure, there is provided an electrode layer for use in an all-solid-state battery, the electrode layer containing an electrode active material, a sulfide solid electrolyte, and a residual liquid, the residual liquid having a Hansen solubility parameter of δ P is 2.9MPa 1 / 2and a boiling point of 190° C. or more.
[0006] According to the present disclosure, the residual liquid δ P Since the boiling point is within a predetermined range, the electrode layer has a good capacity retention rate.
[0007] In the above disclosure, the amount of the residual liquid in the electrode layer may be 1500 ppm or more and 5000 ppm or less.
[0008] In the above disclosure, the residual liquid may include at least one of a naphthalene-based compound, a lauryl group-containing compound, and a monocyclic aromatic compound.
[0009] In the above disclosure, the residual liquid may include the naphthalene-based compound.
[0010] In the above disclosure, the naphthalene-based compound may be tetralin.
[0011] In the above disclosure, the residual liquid may include the lauryl group-containing compound.
[0012] In the above disclosure, the residual liquid may contain the monocyclic aromatic compound.
[0013] In the above disclosure, the electrode layer may be a positive electrode layer.
[0014] In the above disclosure, the electrode layer may be a negative electrode layer.
[0015] The present disclosure also provides an all-solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, wherein at least one of the positive electrode layer and the negative electrode layer is the above-mentioned electrode layer.
[0016] According to the present disclosure, by using the above-described electrode layer, an all-solid-state battery with a good capacity retention rate is obtained. Effect of the Invention
[0017] The present disclosure has an effect of providing an electrode layer having a good capacity retention rate. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The electrode layer and the all-solid-state battery according to the present disclosure will be described in detail below.
[0020] A. Electrode layer The electrode layer in the present disclosure is an electrode layer used in an all-solid-state battery, the electrode layer containing an electrode active material, a sulfide solid electrolyte, and a residual liquid, the residual liquid having a Hansen solubility parameter of δ P is 2.9MPa 1 / 2 and the boiling point is 190°C or higher.
[0021] According to the present disclosure, the residual liquid δ P Since the boiling point is within a predetermined range, the electrode layer has a good capacity retention rate. P corresponds to the dipole-dipole interaction energy between molecules. δ P Residual liquids with a high SP value tend to dissolve the sulfide solid electrolyte, and elements constituting the sulfide solid electrolyte tend to be eluted. For example, in Patent Document 1, 1 / 2 As specific examples of the dispersion medium, various dispersion media such as butyl butyrate are disclosed. When the electrode layer contains butyl butyrate as a residual liquid, the δ PSince δ is relatively large, it reacts with the sulfide solid electrolyte, causing deterioration of the sulfide solid electrolyte (reduction in ionic conductivity). As a result, the charge-discharge cycle characteristics are degraded. In contrast, in the present disclosure, the electrode layer has a δ P Since the electrode layer contains a residual liquid having a small amount of residual liquid, it is possible to suppress a reaction between the residual liquid and the sulfide solid electrolyte, resulting in an electrode layer with a good capacity retention rate.
[0022] Furthermore, when an electrode layer is produced using a dispersion medium with a low boiling point, the dispersion medium is likely to volatilize from the electrode layer during drying, but cracks are likely to occur in the electrode layer. This is thought to be because the binder contained in the electrode layer segregates during drying. In contrast, in the present disclosure, the boiling point of the residual liquid remaining in the electrode layer is high, so that the occurrence of cracks in the electrode layer can be suppressed. In particular, the residual liquid contained in the electrode layer has a boiling point of δ P Since the δ of the dispersion medium is small and the boiling point is high, even if the amount of residual liquid is significantly increased, as described in the examples below, the electrode layer has a good capacity retention rate. P Specific examples of the boiling points are shown in Table 1.
[0023] [Table 1]
[0024] 1. Residual liquid The electrode layer in the present disclosure contains a residual liquid. The residual liquid is a liquid component remaining in the electrode layer. The residual liquid is typically a dispersion medium in a paste described below. The residual liquid is also a component having a Hansen solubility parameter of δ P is 2.9MPa 1 / 2 and has a boiling point of 190° C. or higher. The electrode layer may contain only one type of such residual liquid, or may contain two or more types.
[0025] δ in residual liquid P is usually 2.9MPa 1 / 2 is less than δ P is 2.5MPa 1 / 2It may be less than 2.3MPa 1 / 2 It may be less than 2.1MPa 1 / 2 It may be less than or equal to δ P If the temperature is large, the deterioration of the sulfide electrolyte due to the residual liquid may not be sufficiently suppressed.
[0026] The boiling point of the residual liquid is usually 190°C or higher, may be 200°C or higher, may be 205°C or higher, or may be 210°C or higher. If the boiling point of the residual liquid is low, there is a possibility that cracking of the electrode layer cannot be sufficiently suppressed. On the other hand, the boiling point of the residual liquid is, for example, 300°C or lower, and may be 250°C or lower. If the boiling point of the residual liquid is high, for example, the drying temperature needs to be increased in order to remove the residual liquid, which tends to reduce the production efficiency.
[0027] Examples of the residual liquid include naphthalene compounds, lauryl group-containing compounds, and monocyclic aromatic compounds. The naphthalene compounds are compounds having a naphthalene skeleton, such as tetralin (tetrahydronaphthalene) and naphthalene. The residual liquid may be tetralin or may not be tetralin. The lauryl group-containing compounds are compounds having a lauryl group (dodecyl group), such as N,N-dimethyllaurylamine (N,N-dimethyldodecylamine). The monocyclic aromatic compounds are compounds having a monocyclic aromatic hydrocarbon (typically a benzene ring). The monocyclic aromatic compounds may have one, two, or three or more monocyclic aromatic hydrocarbons. Examples of the monocyclic aromatic compounds include divinylbenzene, tetramethylbenzene (e.g., 1,2,3,5-tetramethylbenzene, 1,2,3,4-tetramethylbenzene), and diphenylmethane.
[0028] The amount of residual liquid in the electrode layer is, for example, 500 ppm or more and 7000 ppm or less, may be 1000 ppm or more and 6000 ppm or less, or may be 1500 ppm or more and 5000 ppm or less. If the amount of residual liquid is small, the electrode layer is likely to crack. On the other hand, even if the amount of residual liquid is large, the effect on the capacity maintenance rate is small, but the volume energy density may relatively decrease. In addition, in the present disclosure, even if the amount of residual liquid is relatively large, the capacity maintenance rate is unlikely to decrease. Therefore, there is also an advantage that the drying process can be simplified when preparing the electrode layer. The amount of residual liquid can be determined by gas chromatography mass spectrometry (GC-MS) as described later.
[0029] 2. Electrode active material The electrode layer in the present disclosure contains an electrode active material. The electrode active material may be a positive electrode active material or a negative electrode active material.
[0030] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc., rock salt layered active materials, LiMn2O4, Li(Ni 0.5 Mn 1.5 Examples of the positive electrode active material include spinel-type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4, and olivine-type active materials such as LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4. The surface of the positive electrode active material is preferably coated with an ion-conductive oxide. This is because it is possible to suppress the reaction between the positive electrode active material and the sulfide solid electrolyte and the generation of a high resistance layer. An example of the ion-conductive oxide is LiNbO3. The thickness of the ion-conductive oxide is, for example, 1 nm or more and 30 nm or less.
[0031] Examples of the negative electrode active material include Li-based active materials such as metallic lithium and lithium alloys; carbon-based active materials such as graphite and hard carbon; oxide-based active materials such as lithium titanate; and Si-based active materials such as simple Si, Si alloys, and silicon oxide (SiO). Lithium titanate (LTO) is a compound containing Li, Ti, and O. The composition of lithium titanate is, for example, Li x Ti y O z (3.5≦x≦4.5, 4.5≦y≦5.5, 11≦z≦13). x may be 3.7 or more and 4.3 or less, or 3.9 or more and 4.1 or less. y may be 4.7 or more and 5.3 or less, or 4.9 or more and 5.1 or less. z may be 11.5 or more and 12.5 or less, or 11.7 or more and 12.3 or less. Lithium titanate is Li4Ti5O 12 It is preferable that the composition is represented by the following formula:
[0032] The shape of the electrode active material may be, for example, particulate. The average particle size (D 50 ) is, for example, 10 nm or more and 50 nm or less, and may be 100 nm or more and 20 μm or less. 50 ) refers to the particle size (median diameter) at the cumulative 50% of the cumulative particle size distribution, and is calculated, for example, from measurements using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM).
[0033] The proportion of the electrode active material in the electrode layer is, for example, 20% by volume or more and 80% by volume or less, or may be 30% by volume or more and 70% by volume or less, or may be 40% by volume or more and 65% by volume or less. If the proportion of the electrode active material is low, the volumetric energy density may be low. On the other hand, if the proportion of the electrode active material is high, the ion conduction path may not be sufficiently formed.
[0034] 3.Sulfide solid electrolyte The electrode layer in the present disclosure contains a sulfide solid electrolyte. The sulfide solid electrolyte constitutes an ion conduction path in the electrode layer. The sulfide solid electrolyte usually contains sulfur (S) as a main component of the anion element. The sulfide solid electrolyte contains, for example, Li, A (A is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, In), and S. It is preferable that A contains at least P. Further, the sulfide solid electrolyte may contain at least one of Cl, Br, and I as a halogen. Also, the sulfide solid electrolyte may contain O.
[0035] The sulfide solid electrolyte may be a glass-based sulfide solid electrolyte, a glass-ceramic-based sulfide solid electrolyte, or a crystalline sulfide solid electrolyte. When the sulfide solid electrolyte has a crystalline phase, examples of the crystalline phase include a Thio-LISICON type crystalline phase, an LGPS type crystalline phase, and an argyrodite type crystalline phase.
[0036] The composition of the sulfide solid electrolyte is not particularly limited, and examples include xLi2S·(100 - x)P2S5 (70 ≤ x ≤ 80), yLiI·zLiBr·(100 - y - z)(xLi2S·(1 - x)P2S5) (0.7 ≤ x ≤ 0.8, 0 ≤ y ≤ 30, 0 ≤ z ≤ 30).
[0037] The sulfide solid electrolyte has a general formula: Li 4-x Ge 1-x P x It may have a composition represented by S4 (0 < x < 1). In the above general formula, at least a part of Ge may be substituted with at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. In the above general formula, at least a part of P may be substituted with at least one of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. In the above general formula, a part of Li may be substituted with at least one of Na, K, Mg, Ca, and Zn. In the above general formula, a part of S may be substituted with a halogen (at least one of F, Cl, Br, and I).
[0038] Other compositions of sulfide solid electrolytes include, for example, Li 7-x-2y P.S. 6-x-y X y , Li 8-x-2y SiS 6-x-y X y , Li 8-x-2y GeS 6-x-y X y In these compositions, X is at least one of F, Cl, Br and I, and x and y satisfy 0≦x, 0≦y.
[0039] The sulfide solid electrolyte preferably has high Li-ion conductivity. The Li-ion conductivity of the sulfide solid electrolyte at 25° C. is, for example, 1×10 -4 S / cm or more, 1×10 -3 The sulfide solid electrolyte preferably has high insulating properties. The electronic conductivity of the sulfide solid electrolyte at 25° C. is, for example, 10 -6 S / cm or less, 10 -8 S / cm or less, -10 The sulfide solid electrolyte may have a shape of, for example, a particulate shape. The average particle diameter (D 50 ) is, for example, 0.1 μm or more and 50 μm or less.
[0040] The proportion of the sulfide solid electrolyte in the electrode layer is, for example, 15 volume % or more and 75 volume % or less, and may be 15 volume % or more and 60 volume % or less. If the proportion of the sulfide solid electrolyte is low, there is a possibility that the ion conduction path is not sufficiently formed. On the other hand, if the proportion of the sulfide solid electrolyte is high, there is a possibility that the volumetric energy density is low.
[0041] The ratio of the electrode active material to the total of the electrode active material and the sulfide solid electrolyte is, for example, 40% by volume or more and 80% by volume or less, or may be 50% by volume or more and 80% by volume or less, or may be 60% by volume or more and 70% by volume or less. If the ratio of the electrode active material is low, the volumetric energy density may be low. On the other hand, if the ratio of the electrode active material is high, the ion conduction path may not be sufficiently formed.
[0042] The total proportion of the electrode active material and the sulfide solid electrolyte in the electrode layer is, for example, 75 vol.% or more and less than 100 vol.%, may be 80 vol.% or more and less than 100 vol.%, or may be 90 vol.% or more and less than 100 vol.%.
[0043] 4. Electrode layer The electrode layer in the present disclosure contains the above-mentioned electrode active material, sulfide solid electrolyte, and residual liquid. The electrode layer may be a positive electrode layer or a negative electrode layer.
[0044] The electrode layer in the present disclosure may contain a conductive material. Examples of the conductive material include carbon materials, metal particles, and conductive polymers. Examples of the carbon material include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF). The proportion of the conductive material in the electrode layer is, for example, 0.1% by volume or more and 10% by volume or less, and may be 0.3% by volume or more and 10% by volume or less.
[0045] The electrode layer in the present disclosure may contain a binder. Examples of the binder include fluorine-based binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), and rubber-based binders such as acrylate butadiene rubber (ABR) and styrene butadiene rubber (SBR). The proportion of the binder in the electrode layer is, for example, 1% by volume or more and 20% by volume or less, and may be 5% by volume or more and 20% by volume or less. The thickness of the electrode layer is, for example, 0.1 μm or more and 1000 μm or less.
[0046] The method for producing an electrode layer in the present disclosure is not particularly limited. In the present disclosure, a method for producing an electrode layer used in an all-solid-state battery includes a preparation step of preparing a paste containing an electrode active material, a sulfide solid electrolyte, and a dispersion medium, a coating step of coating the paste to form a coating layer, and a drying step of drying the coating layer to remove the dispersion medium, and the dispersion medium is a solubility parameter having a solubility of δ P is 2.9MPa 1 / 2 It is also possible to provide a method for producing an electrode layer in which the viscosity of the paste is less than 100 psig and the boiling point is 190°C or higher. The paste may further contain at least one of a conductive material and a binder. The method for applying the paste is not particularly limited, but may be, for example, a blade method. The drying temperature of the coating layer is, for example, 80°C or higher and 120°C or lower. The drying time of the coating layer is, for example, 10 minutes or longer and 5 hours or shorter. In addition, it is preferable that the residual amount of the dispersion medium (residual liquid amount) in the electrode layer is within the above-mentioned range.
[0047] B. All-solid-state battery Fig. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. The all-solid-state battery 10 shown in Fig. 1 includes a positive electrode layer 1, a negative electrode layer 2, a solid electrolyte layer 3 disposed between the positive electrode layer 1 and the negative electrode layer 2, a positive electrode current collector 4 that collects current from the positive electrode layer 1, and a negative electrode current collector 5 that collects current from the negative electrode layer 2. In the present disclosure, at least one of the positive electrode layer 1 and the negative electrode layer 2 is the electrode layer described above in "A. Electrode layer".
[0048] According to the present disclosure, by using the above-described electrode layer, an all-solid-state battery with a good capacity retention rate is obtained.
[0049] 1. Positive and negative electrode layers The positive electrode layer and the negative electrode layer in this disclosure are the same as those described in "A. Electrode layer" above, and therefore the description here is omitted. In this disclosure, (i) the positive electrode layer may correspond to the above-mentioned electrode layer, and the negative electrode layer may not correspond to the above-mentioned electrode layer, (ii) the positive electrode layer may not correspond to the above-mentioned electrode layer, and the negative electrode layer may correspond to the above-mentioned electrode layer, and (iii) both the positive electrode layer and the negative electrode layer may correspond to the above-mentioned electrode layer.
[0050] 2.Solid electrolyte layer The solid electrolyte layer in the present disclosure is disposed between the positive electrode layer and the negative electrode layer. The solid electrolyte layer contains at least a solid electrolyte, and may further contain a binder. The solid electrolyte and the binder are the same as those described in "A. Electrode Layer" above, and therefore will not be described here. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.
[0051] 3.All-solid-state battery In the present disclosure, the term "all-solid-state battery" refers to a battery having a solid electrolyte layer (at least a layer containing a solid electrolyte). The all-solid-state battery in the present disclosure also includes a power generating element having a positive electrode layer, a solid electrolyte layer, and a negative electrode layer. The power generating element usually has a positive electrode current collector and a negative electrode current collector. The positive electrode current collector is disposed, for example, on the surface of the positive electrode layer opposite to the solid electrolyte layer. Examples of the material for the positive electrode current collector include metals such as aluminum, SUS, and nickel. Examples of the shape of the positive electrode current collector include foil and mesh. On the other hand, the negative electrode current collector is disposed, for example, on the surface of the negative electrode layer opposite to the solid electrolyte layer. Examples of the material for the negative electrode current collector include metals such as copper, SUS, and nickel. Examples of the shape of the negative electrode current collector include foil and mesh.
[0052] The all-solid-state battery in the present disclosure may include an exterior body that houses the power generating element. Examples of the exterior body include a laminate-type exterior body and a case-type exterior body. The all-solid-state battery in the present disclosure may also include a restraining jig that applies a restraining pressure in the thickness direction to the power generating element. A known jig can be used as the restraining jig. The restraining pressure may be, for example, 0.1 MPa or more and 50 MPa or less, and may be 1 MPa or more and 20 MPa or less. If the restraining pressure is small, there is a possibility that a good ion conductive path and a good electron conductive path will not be formed. On the other hand, if the restraining pressure is large, the restraining jig may become large, and the volumetric energy density may decrease.
[0053] The type of all-solid-state battery in the present disclosure is not particularly limited, but is typically a lithium-ion secondary battery. The use of the all-solid-state battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, it is preferable to use the all-solid-state battery as a driving power source for hybrid electric vehicles, plug-in hybrid electric vehicles, or electric vehicles. In addition, the all-solid-state battery in the present disclosure may be used as a power source for moving bodies other than vehicles (for example, railways, ships, and aircraft), and may be used as a power source for electrical products such as information processing devices.
[0054] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0055] [Experimental Example 1] Tetralin (δ PA sulfide solid electrolyte (10LiI 15LiBr 75 (0.75Li2S 0.25P2S5)) was added to a sintered body (pH 7.0, boiling point 205°C) and mixed using an ultrasonic homogenizer (UH-50, manufactured by SMT) to obtain a dispersion. The solid content was then separated using a centrifuge to obtain a solution.
[0056] [Experimental Example 2] Instead of tetralin, butyl butyrate (δ P A solution was obtained in the same manner as in Experimental Example 1, except that a toluene solution (NaCl, boiling point 165° C.) was used.
[0057] [evaluation] The amount of Li in the solutions obtained in Experimental Examples 1 and 2 was determined by acid decomposition / ICP atomic emission spectrometry (acid decomposition / ICP-AES). The amount of S in the solutions obtained in Experimental Examples 1 and 2 was determined by oxygen combustion / ion chromatography. The results are shown in Table 2. The amount of Li and the amount of S shown in Table 2 are relative values when the result of Experimental Example 1 is set to 1.
[0058] [Table 2]
[0059] As shown in Table 2, tetralin has a δ P It was confirmed that the reactivity with the sulfide solid electrolyte is low because the valence is small.
[0060] [Example 1] Li4Ti5O as negative electrode active material 12 The negative electrode active material, conductive material (VGCF), binder (PVdF) and dispersion medium (tetralin, δ P= 2.0, boiling point 205 ° C) was weighed and mixed for 30 minutes using an ultrasonic homogenizer (UH-50 manufactured by SMT). Then, a sulfide solid electrolyte (LiI-LiBr-Li2S-P2S5-based glass ceramic) was added, and mixed again for 30 minutes using an ultrasonic homogenizer (UH-50 manufactured by SMT). This resulted in a negative electrode paste. Next, the negative electrode paste was applied onto a negative electrode current collector (Ni foil). After application, it was dried on a hot plate at 100 ° C for 30 minutes. This resulted in a negative electrode layer being formed on the negative electrode current collector.
[0061] [Comparative Example 1] Instead of tetralin, xylene (δ P A negative electrode layer was formed on a negative electrode current collector in the same manner as in Reference Example 3, except that a volatile organic compound (VOC) was used.
[0062] [evaluation] The surfaces of the negative electrode layers produced in Example 1 and Comparative Example 1 were observed to confirm the occurrence of cracks. The results are shown in Table 3.
[0063] [Table 3]
[0064] As shown in Table 3, in Example 1, no cracks occurred in the negative electrode layer, but in Comparative Example 1, cracks occurred in the negative electrode layer. The reason for this is presumably because xylene has a low boiling point, and therefore a large amount of volatilization occurred in a short time during drying. In contrast, tetralin has a high boiling point, and therefore, it is presumably because a large amount of volatilization did not occur in a short time during drying.
[0065] [Example 2] (Preparation of positive electrode paste) The positive electrode active material is LiNi with a surface treatment of LiNbO3. 1 / 3 Co 1 / 3 Mn 1 / 3 The positive electrode active material, conductive material (VGCF), sulfide solid electrolyte (LiI-LiBr-Li2S-P2S5 glass ceramic), binder (PVdF) and dispersion medium (tetralin, δP = 2.0, boiling point 205°C) were mixed using an ultrasonic homogenizer (UH-50 manufactured by SMT Co., Ltd.) to obtain a positive electrode paste.
[0066] (Preparation of negative electrode paste) Li4Ti5O as negative electrode active material 12 The negative electrode active material, conductive material (VGCF), binder (PVdF) and dispersion medium (tetralin, δ P = 2.0, boiling point 205 ° C.) was weighed and mixed for 30 minutes using an ultrasonic homogenizer (UH-50 manufactured by SMT). Then, a sulfide solid electrolyte (LiI-LiBr-Li2S-P2S5-based glass ceramic) was added, and mixed again for 30 minutes using an ultrasonic homogenizer (UH-50 manufactured by SMT). This produced a negative electrode paste.
[0067] (Preparation of SE layer paste) A polypropylene container was filled with a dispersion medium (heptane), a binder (heptane solution containing 5% by mass of butadiene rubber-based binder), and a sulfide solid electrolyte (LiI-LiBr-Li2S-P2S5-based glass ceramic, average particle size D 50 The mixture was mixed for 30 seconds using an ultrasonic homogenizer (UH-50 manufactured by SMT Corporation). The container was then shaken for 3 minutes using a shaker. This resulted in a paste for a solid electrolyte layer (a paste for an SE layer).
[0068] (Production of all-solid-state batteries) First, the positive electrode paste was applied onto the positive electrode collector (aluminum foil) by the blade method using an applicator. After application, the paste was dried on a hot plate at 50°C for 10 minutes, and then dried on a hot plate at 100°C for 10 minutes. This resulted in a positive electrode having a positive electrode collector and a positive electrode layer. Next, the negative electrode paste was applied onto the negative electrode collector (Ni foil). After application, the paste was dried on a hot plate at 50°C for 10 minutes, and then dried on a hot plate at 100°C for 10 minutes. This resulted in a negative electrode having a negative electrode collector and a negative electrode layer. Here, the basis weight of the negative electrode layer was adjusted so that the specific charge capacity of the negative electrode was 1.15 times the specific charge capacity of the positive electrode when the specific charge capacity of the positive electrode was 185mAh / g.
[0069] Next, the positive electrode was pressed. The surface of the pressed positive electrode layer was coated with a paste for the SE layer by a die coater, and dried on a hot plate at 100°C for 30 minutes. Then, roll pressing was performed at a linear pressure of 5 ton / cm. This resulted in a positive electrode side laminate having a positive electrode current collector, a positive electrode layer, and a solid electrolyte layer. Next, the negative electrode was pressed. The surface of the pressed negative electrode layer was coated with a paste for the SE layer by a die coater, and dried on a hot plate at 100°C for 30 minutes. Then, roll pressing was performed at a linear pressure of 5 ton / cm. This resulted in a negative electrode side laminate having a negative electrode current collector, a negative electrode layer, and a solid electrolyte layer.
[0070] The positive electrode side laminate and the negative electrode side laminate were each punched and arranged so that the solid electrolyte layers faced each other, and an unpressed solid electrolyte layer was placed between them. Then, they were roll pressed at 130°C with a linear pressure of 2 ton / cm to obtain a power generating element having a positive electrode, a solid electrolyte layer, and a negative electrode in this order. The obtained power generating element was laminated and sealed, and restrained at 5 MPa to obtain an all-solid-state battery.
[0071] [Example 3] An all-solid-state battery was produced in the same manner as in Example 2, except that the drying conditions for producing the positive electrode layer and the negative electrode layer were changed to drying on a hot plate at 80° C. for 10 minutes and then drying on a hot plate at 110° C. for 10 minutes, respectively.
[0072] [Comparative Example 2] As a dispersion medium, butyl butyrate (δ P Positive electrode paste and negative electrode paste were prepared in the same manner as in Example 2, except that a sintered body (water, sintered body, etc.) was used (pH 7.0, boiling point 165°C). Using each of the prepared pastes, all-solid-state batteries were prepared in the same manner as in Example 2, except that the drying conditions for preparing the positive electrode layer and the negative electrode layer were changed to drying on a hot plate at 100°C for 30 minutes.
[0073] [Comparative Example 3] An all-solid-state battery was produced in the same manner as in Comparative Example 2, except that the drying conditions for producing the positive electrode layer and the negative electrode layer were changed to drying for 15 minutes on a hot plate at 100° C., respectively.
[0074] [Comparative Example 4] An all-solid-state battery was produced in the same manner as in Comparative Example 2, except that the drying conditions for producing the positive electrode layer and the negative electrode layer were changed to drying on a hot plate at 95° C. for 30 minutes, respectively.
[0075] [Comparative Example 5] An all-solid-state battery was produced in the same manner as in Comparative Example 2, except that the drying conditions for producing the positive electrode layer and the negative electrode layer were changed to drying on a hot plate at 90° C. for 30 minutes, respectively.
[0076] [evaluation] (Measurement of residual liquid volume) The active material layers (positive and negative electrode layers) were taken out from the electrodes (positive and negative electrodes) prepared in Examples 2 and 3 and Comparative Examples 2 to 5, and stirred with methanol. Then, a solution was obtained by separating the solid matter using a centrifuge. The amount of residual liquid (amount of residual dispersion medium) in the obtained solution was determined by gas chromatography-mass spectrometry (GC-MS). The results are shown in Table 4.
[0077] (Capacity retention rate measurement) The capacity retention rate of the all-solid-state batteries prepared in Examples 2 and 3 and Comparative Examples 2 to 5 was measured. Specifically, the all-solid-state batteries were charged at a constant current equivalent to 0.3 C, and after the cell voltage reached 2.7 V, they were charged at a constant voltage, and the charging was terminated when the charging current reached 0.01 C. Thereafter, they were discharged at a constant current equivalent to 0.3 C, and the charging was terminated when the charging current reached 1.5 V. This discharge capacity was taken as the discharge capacity of the first cycle. Thereafter, five cycles of charging and discharging were performed under the same conditions, and the discharge capacity of the fifth cycle was obtained. The capacity retention rate was obtained by dividing the discharge capacity of the fifth cycle by the discharge capacity of the first cycle. The results are shown in Table 4.
[0078] [Table 4]
[0079] As shown in Table 4, it was confirmed that the all-solid-state batteries produced in Examples 2 and 3 had a higher capacity retention rate than the all-solid-state batteries produced in Comparative Examples 2 to 5. It was also confirmed that in Comparative Examples 2 to 5, the capacity retention rate decreased with an increase in the amount of residual liquid. On the other hand, in Example 2, an electrode layer with a larger amount of residual liquid than in Comparative Example 5 was used, but a high capacity retention rate of 98% was confirmed. [Explanation of symbols]
[0080] 1 ... Positive electrode layer 2 ... Negative electrode layer 3...Solid electrolyte layer 4...Positive electrode current collector 5...Negative electrode current collector 10...All-solid-state battery
Claims
1. An electrode layer for use in an all-solid-state battery, The electrode layer contains an electrode active material, a sulfide solid electrolyte, and a residual liquid, The residual liquid has a Hansen solubility parameter δP of 2.9 MPa. 1/2 and a boiling point of 190° C. or more; The amount of the residual liquid in the electrode layer is 1500 ppm or more and 5000 ppm or less.
2. The electrode layer according to claim 1 , wherein the residual liquid comprises at least one of a naphthalene-based compound, a lauryl group-containing compound, and a monocyclic aromatic compound.
3. The electrode layer of claim 2 , wherein the residual liquid comprises the naphthalene-based compound.
4. The electrode layer according to claim 3 , wherein the naphthalene-based compound is tetralin.
5. The electrode layer of claim 1 , wherein the residual liquid is free of tetralin.
6. The electrode layer of claim 2 , wherein the residual liquid comprises the lauryl group-containing compound.
7. The electrode layer according to claim 2 , wherein the residual liquid comprises the single ring aromatic compound.
8. The electrode layer according to claim 1 , wherein the electrode layer is a positive electrode layer.
9. The electrode layer according to claim 1 , wherein the electrode layer is a negative electrode layer.
10. An all-solid-state battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, An all-solid-state battery, wherein at least one of the positive electrode layer and the negative electrode layer is the electrode layer according to any one of claims 1 to 9.
Citation Information
Patent Citations
Sulfide solid battery
JP2018006051A
Electrode mixture, battery, and electrode manufacturing method
JP2019133923A
All-solid battery
JP2021132010A
Solid electrolyte composition, all-solid secondary battery sheet, all-solid secondary battery, and method of manufacturing all-solid secondary battery sheet or all-solid secondary battery
WO2019203334A1
Solid electrolyte and battery using same
WO2020100465A1